Treatment safety of ART cycles with extremely high oestradiol concentrations using GnRH agonist trigger. Issue 3 (March 2023) - Youngster, Michal; Kedem, Alon; Avraham, Sarit; Yerushalmi, Gil; Baum, Micha; Maman, Ettie; Hourvitz, Ariel; Gat, Itai
Abstract: Research question: Are IVF treatments with extremely high peak oestradiol levels and gonadotrophin releasing hormone (GnRH) agonist trigger associated with higher complication rates? Design: A retrospective cohort study including patients from two large medical centres treated between 2019 and 2021. A study group with extremely high peak oestradiol levels (≥20, 000 pmol/l on the day of ovarian stimulation, or ≥15, 000 pmol/l on the previous day) and a control group with normal range oestradiol levels (3000–12000 pmol/l) that received GnRH agonist triggering. Patients were surveyed about complaints and medical care related to ovum retrieval and medical files were reviewed. Major complication rates and the need for medical assistance were compared. Results: Several differences between the study and control group were observed because of the study design: mean age was 33.01 ± 5.14 versus 34.57 ± 4.52 ( P < 0.001), mean peak oestradiol levels was 26645.34 ± 8592.57 pmol/l versus 7229.75 ± 2329.20 pmol/l ( P < 0.001), and mean number of oocytes were 27.55 ± 13.46 versus 11.67 ± 5.76 ( P < 0.001) for the study and control group, respectively. Major complications and hospitalization rates were similar between the study and control groups (three [1.25%] versus one [0.48%]; P  = 0.62 and three [1.25%] versus two [0.96%]; P  = 1.0, respectively). Thirty-six patients (15.1%) in the study group and 11 (5.3%) in the control group sought medical care after retrieval, mostly due to abdominal pain, without the need for further workup or hospitalization ( P < 0.001). Conclusions: Extremely high oestradiol levels were not associated with thromboembolic events, higher major complication or hospitalization rates, and therefore may be considered safe. Nevertheless, patients may be informed of possible higher rates of discomfort, mostly abdominal pain. Larger studies are warranted to confirm our results.